Strategies to prevent HIV transmission to serodiscordant couples - Ronaldo Campos Hallal; Juan Carlos Raxach; Nêmora Tregnago Barcellos; Ivia Maksud (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACTIntroduction:The use antiretroviral reduces the sexual transmission of HIV, expanding interventions for serodiscordant couples.Objective:This article aims to review the use of antiretroviral and other prevention interventions among serodiscordant couples and to analyze its use in Brazil.Methods:A retrospective review was performed through the MEDLINE database and bases included in the Biblioteca Virtual em Saúde.Results:The articles recovered exhibit four main strategies: (1) condom; (2) reduction of risks in sexual practices; (3) use of antiretrovirals, particularly early initiation of antiretroviral therapy (TASP) and pre-exposure prophylaxis (PrEP); (4) risk reduction in reproduction.Discussion:TASP is highly effective in reducing sexual transmission, PrEP was tested in serodiscordant couples and both reduce the sexual transmission risk in different sexual practices, enabling individualized prevention strategies.Conclusions:When used in combination, antiretrovirals and sexual practices with condoms offer greater efficacy than any single strategy. The combined use of new and old strategies allows us to build a prevention policy for all.